Developing graduate attributes through the application of coaching theory - Iain Thomas Killoughery; Patrick W. C. Lau; Peng Zhou (Journal of Teaching and Learning for Graduate Employability)
Graduate attributes (GAs) have been formally adopted by higher education institutions for some time and describe the skills and competences that students should develop over the course of their studies. GAs are considered to be important to universities as they act as a means to represent and extend their brand, while also providing a channel to maintain connection with industry. However, despite regular engagement with industry, employers remain unsatisfied with graduate transferable skills. This may be caused by a lack of a common theoretical underpinning to develop such attributes. Therefore, the aim of this study was to provide an evidence-based methodology which develops transferable skills in university graduates. Two classes at a public university in Hong Kong were used in this study. One class received a 12-week intervention incorporating a variety of coaching activities. The second class acted as a control group. Students were asked to complete pre-intervention surveys which provided self-reports of current ratings in GAs and resourcefulness behaviours. After completion of the 12-week intervention, students were asked to complete post-intervention surveys, again reporting self-ratings on the same topics. Survey data was analysed to identify changes in student scores, which highlighted improvements in all graduate attribute ratings post-intervention. Furthermore, help-seeking behaviours were shown to have significant improvement post intervention. The findings of this study suggest that coaching practices may provide an efficient and effective way to develop transferable skills in students, and this paper provides discussion on the implications of these results.